Unmet Need for Prevention of Unwanted Pregnancy in Shiraz - Fariba Moradi; Zohreh Balaghi; Hassan Joulaei; Najaf Zare; Samad Mohammadi; Mohsen Moghadami (Shiraz University of Medical Sciences, 2014)
Background: Prevention of unwanted pregnancy is a key strategy to improve the women's health through spacing of birth and avoiding pregnancy at high-risk maternal ages. Unmet need by definition is the percentage of fecund married women who are not using contraceptives while they do not want to get pregnant. They do this due to unavailable quality services, limited choice of methods, lack of information, safety concerns or side-effects and partner disapproval. The present study aimed to assess the magnitude of unmet need for prevention of unwanted pregnancy in Shiraz.Methods: In this descriptive cross-sectional study, 2000 married women of childbearing age (10-49 years) were selected randomly in a survey in Shiraz. Data collection was done using a researcher-made questionnaire and the results were reported using descriptive statistical methods.Results: In the present study, 85.6% of the women used a contraceptive method. 58.7% of them used modern methods of contraception. Reported reasons for not using contraceptives included recent delivery (25%), intention to have more children (20.6%), lack of awareness about contraceptive methods or where such services were offered (6.3%) and irregular sexual intercourse with husband (4.5%). Interrupted intercourse ranked the highest among the methods used. Finally, the unmet need for prevention of unwanted pregnancy in this study was reported to be 4.3 percent.Conclusion: Women in Shiraz had a relatively lower level of unmet need. Counseling is recommended for higher risk women with unmet need in order to keep the descending trend of unmet need for prevention of unwanted pregnancy in Shiraz.